Creation of ESQK Learning Model as an Effort to Improve Multi Intelligence - Ujang Maulana Yusup (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Increasing students' multi-intelligence lies in the ability and quality of the learning process applied. The learning process will be more meaningful if there is a balance between knowledge, attitudes and skills. One learning model that is able to implement balance is ESQK, which is a combination of several intelligence abilities IQ, EQ, SQ and kinesthetic intelligence which become one unit with the aim of improving multi-intelligence. There are four skills that must be improved in learning to be successful in life 1) creative rational thinking skills, 2) emotional management skills, 3) skills to gain meaning in life in all events, and 4) dynamic physical management skills. ESQK was developed based on current theories about how students should learn meaningfully so that it can be applied in the real world. This model is a model that is easy for teachers to use and can provide an opportunity to develop creativity in learning models that can improve students' multi-intelligence